PENGARUH GAYA KEPEMIMPINAN TERHADAP DISIPLIN SISWA DI SMA ISLAM JAUHARUL FALAH AL-ISLAMY DESA SUNGAI TERAP - Sakinah, Rita; Yudha, Redi Indra (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of the principal's leadership style on the discipline of students at the Islamic SMAjauharul Falah Al-Islamy Sungai Terap Village, Kumpeh Ulu District, Muaro Jambi Regency. The research method used in this research is a quantitative method using simple linear regression analysis techniques. The results of the research show that leadership style has a significant and positive effect on student discipline at the Islamic SMAjauharul Falah Al-Islamy, Sungai Terap Village, Kumpeh Ulu District, Muaro Jambi Regency.